Enabling positive tipping points in public support for food system transformation: The case of meat consumption - Fesenfeld, Lukas Paul; Sun, Yixian (International Food Policy Research Institute, 2023)
Today’s food production and consumption has large consequences for the environment and human health. With respect to climate change, our food system is now responsible for at least a third of the global anthropogenic greenhouse gas (GHG) emissions. In particular, the production of red meat has become the largest source of methane, which is a powerful short-lived GHG. Livestock production is also the single largest driver of habitat loss, and a leading cause of soil erosion, water, and nutrient pollution across the world, which increasingly compound pressures on ecosystems and biodiversity. In addition, scientific evidence suggests strong associations between meat consumption and health risks including total mortality, cardiovascular diseases, colorectal cancer, and type 2 diabetes. This issue of overconsumption is particularly salient for developed countries and large emerging economies where meat consumption is high (i.e., >20–30kg per person per year). Recent systematic reviews suggest that domestic demand in countries with tropical rainforests cause a significant proportion of agriculturally driven tropical deforestation. Hence, rapid dietary changes toward more plant-based diets are a critical component of global food system transformation as they hold the promise to make important contributions to solving health, climate, and ecological crises. Without such changes, achieving the Paris Agreement targets and many Sustainable Development Goals (SDGs) is unlikely, even if all other sectors were to achieve rapid transition toward sustainability.